Kompetensi Komunikasi Interpersonal Karyawan Coffee Shop Delapan Meter dan Toko Kopi Bersaudara dalam Interaksi dengan Pelanggan - Gagastama Nanglares; Imanuel Deny Krisna Aji (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Interpersonal communication competence is an important aspect in the coffee shop business which can have an impact on productivity, service quality, customer satisfaction, and even customer loyalty. Toko Kopi Bersaudara features a unique concept by combining coffeeshop and space. Meanwhile, Eight Meter Coffeeshop has a minimalist and elegant concept with complete facilities such as meeting rooms, VIP rooms and smoking rooms. This research aims to analyze the interpersonal communication competence of employees in two coffeeshops with different characteristics. Exploration of the differences in characteristics between the two coffeeshops in relation to the interpersonal communication competence of employees in each place. Research method with a positivism paradigm, quantitative approach. Through data analysis with descriptive statistics, data was collected using a survey method using a questionnaire. The results of the research illustrate that the Kopi Bersaudara shop has a higher value on the dimensions of interpersonal competence than the Eight Meter Coffee Shop. Suggestions that can be given are that the Eight Meter Coffee Shop must review the performance of its employees and provide training on how to behave appropriately towards customers.